Sistem Rekrutmen Tenaga Pendidik dalam Meningkatkan Mutu Pendidikan - Rosyana, Rosyana; Citraningsih, Diningrum; Wiranata, Rz. Ricky Satria (Universitas Islam Negeri Walisongo, 2023)
This study aims to describe and analyze the recruitment system of educators at SDIT Salsabila 3 Banguntapan Yogyakarta, and improve the quality of education through the recruitment system of educators. The study employed a qualitative descriptive methodology. Data was collected through interviews, observations, and document analysis from a selected group of school staff. The results showed that the recruitment system for educators at SDIT Salsabila 3 Banguntapan Yogyakarta was described in several stages, namely, administration, interview stages, and reading and writing the Qur'an and micro teaching. The school is looking for qualified educators according to the profile and has a teaching commitment to improve the quality of education at SDIT Salsabila 3 Banguntapan. The school's efforts in improving quality by conducting development programs for educators and evaluation activities every week. The school provides facilities in developing the talents and interests of students with extracurricular and simaan activities to increase memorization which is carried out twice a week. The implications of recruiting educators have loyalty and commitment in teaching. Before prospective educators officially become educators at SDIT Salsabila 3 Banguntapan make a work contract agreement first according to the applicable work agreement